One-step transformation of MnO2 into MnO2−x@carbon nanostructures for high-performance supercapacitors using structure-guided combustion waves. Issue 26 (15th June 2017) - Shin, Jungho; Shin, Dongjoon; Hwang, Hayoung; Yeo, Taehan; Park, Seonghyun; Choi, Wonjoon
Abstract : Structure-guided combustion waves transform MnO2 nanoparticles into core–shell nanostructures of reduced manganese oxides and carbon layer for high performance supercapacitors. Abstract : The manipulation of micro/nanostructured metal oxides is crucial to advancing their diverse applications, including as electrodes in supercapacitors or batteries, catalysts, and pigments. However, controlling the physicochemical properties of metal oxides requires complex procedures with bulky setups that incur high costs and long processing times. Herein, we present a facile one-step manipulation of the reduced states of manganese oxides and the synthesis of carbon coatings surrounding them, using structure-guided combustion waves (SGCWs), which is induced by incomplete combustion through the chemical fuel-wrapped materials. Controlled oxygen release from MnO2 using SGCWs in air and in an Ar atmosphere enabled direct fabrication of reduced Mn2 O3 /Mn3 O4 /MnO and MnO, respectively. Furthermore, control of the incompletely combusted carbonaceous fuel facilitated the synthesis of carbon coating layers to form Mn2 O3 /Mn3 O4 /MnO@C and MnO@C. These core–shell nanostructures of reduced manganese oxides and carbon layers were applied as supercapacitor electrodes. These electrodes showed better specific capacitance (maximum 438 F g −1 at 10 mV s −1 scan rate for Mn2 O3 /Mn3 O4 /MnO@C) and improved stability in charge–discharge performance compared with bare MnO2, due to the carbon coatings enhancing electrical conductivity in the percolation network of electrodes and facilitating the reversible redox reaction without degradation during cycling operations. SGCWs are applicable for fast, low-cost, and large-scale fabrication of reduced metal oxides and organic material coatings, which could significantly contribute to electrochemical applications.